WHEN GOD TALKS BACK. UNDERSTANDING THE AMERICAN ENGANGELICAL RELATIONSHIP WITH GOD. ALFRED A KNOPF, NEW YORK. - Tanya Luhrmann; Reviewed by: Hatib Abdul Kadir (Al-Albab, 2012)
This book is started with the main question, how come some people in the USA believe in an invisible being, that is God. How has belief in God come to influence people’s lives? How has God come to be really present in human life? Almost 100 percent people in the US, believe in God according to a Gallup Poll (Luhrmann, 2012: xi). In addition, religious enthusiasm for American has grown increasingly rapidly. Throughout the 20th century, American churches and congregations have developed remarkably (Luhrmann, 14). Even Luhrmann gives an example about the paradoxical things. Many people thought that the hippie vision would bring radical revolutionaries movement that threated the right wing. As a contrary, Christian Hippies play significant roles in making religion to be able publicly accepted (even though there were on drugs) (Luhrmann 16-17)